2012
DOI: 10.1111/j.1524-4725.2012.02507.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Invasive Squamous Cell Carcinomas in Biopsy-Proven Squamous Cell Carcinomas In Situ Sent for Mohs Micrographic Surgery

Abstract: Background Squamous cell carcinoma (SCC) in situ (SCCIS) is often treated without any pathologic confirmation of tumor clearance. It is unclear how often an invasive SCC is harbored within a lesion in which the initial biopsy demonstrated SCCIS because of inadequate sampling. This study examines the final histologic diagnosis of cases in which the initial biopsies were diagnosed as SCCIS and evaluates factors that may correlate with a histologic upstaging of the diagnosis. Methods We prospectively recruited 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…One argument against nonsurgical treatment is that it may treat without pathological confirmation of clearance, with a possibility that invasive SCC is harboured within a lesion . Our current study evaluated the frequency of invasive SCC in patients with initial biopsy‐proven SCCIS undergoing surgical re‐excision.…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…One argument against nonsurgical treatment is that it may treat without pathological confirmation of clearance, with a possibility that invasive SCC is harboured within a lesion . Our current study evaluated the frequency of invasive SCC in patients with initial biopsy‐proven SCCIS undergoing surgical re‐excision.…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…These events are often accompanied by high morbidity and mortality. 54 Furthermore, the treatment of recurrent SCC by MMS is far superior to that by standard excision; only 10% of recurrent lesions treated by MMS recur, whereas 23.3% of those treated with wide excision recur. 50,51 Indications for MMS include: (i) lesions located on the scalp, nose, ear, eye, lip, hand or nail unit; (ii) aggressive histological subtypes of SCC; (iii) ill-defined tumors or tumors of >2.0 cm at any location; and (iv) recurrent cancer at any location.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…53 Another study showed that MMS should be considered even for SCC in situ (rather than locally destructive therapies such as cautery and electrodessication) because 31% of these lesions are eventually found to have invasive components on histopathology. 54 Furthermore, the treatment of recurrent SCC by MMS is far superior to that by standard excision; only 10% of recurrent lesions treated by MMS recur, whereas 23.3% of those treated with wide excision recur. 53 A disadvantage of MMS is that it usually cannot capture micrometastases.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Finally, some patients might argue against re-excising a skin cancer when the biopsy margin is reported as clear. However, we have to realize that dermatopathologists are also pressured by dermatologists to give them margins on their shave biopsy samples, probably in many cases for reimbursement purposes; however, as can be seen from this study, or from the previous studies by Kimyai-Asadi and colleagues, 2 Holmkvist and colleagues, 7 or Chuang and colleagues, 8 such margins are not always reliable and Mohs surgery, when appropriate, remains the gold standard treatment for nonmelanoma skin cancers.…”
Section: Discussionmentioning
confidence: 76%